2020
DOI: 10.1007/s40145-020-0378-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the radial resonance frequency spectra of the PZT-based (Zr/Ti = 52/48) piezoceramic thin disks

Abstract: In this paper, both the 1D radial mode and the equivalent circuit of a piezoceramic disk resonator were theoretically analyzed based on IEEE standards. And then, the radial resonance frequency spectra of the PZT-based (Nb/Ce co-doped Pb(Zr 0.52 Ti 0.48)O 3 , abbreviated as PZT-NC) piezoceramic circular disks were measured by an impedance analyzer. A set of resonance frequency spectra including six electrical parameters: Z, R, X, Y, G, and B, were used for making a value distinction between three possible reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…For PZT-5A piezoceramic used here, the planar coupling factor, k p , for planar extension is 0.60 and Kunkel et al [ 33 ] showed that the radial modes for such a high k p value are difficult to suppress. At k p = 0.60, f A /f R is equal to 1.19 using an expression, k p 2 = 1.51 − f R /2f A − (f R /f A ) 2 from Chen et al [ 35 ] and is in the same range as the observed ratios of 1.08 to 1.15 for the PZT disks observed above. For R15, it was 1.15 to 1.27.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…For PZT-5A piezoceramic used here, the planar coupling factor, k p , for planar extension is 0.60 and Kunkel et al [ 33 ] showed that the radial modes for such a high k p value are difficult to suppress. At k p = 0.60, f A /f R is equal to 1.19 using an expression, k p 2 = 1.51 − f R /2f A − (f R /f A ) 2 from Chen et al [ 35 ] and is in the same range as the observed ratios of 1.08 to 1.15 for the PZT disks observed above. For R15, it was 1.15 to 1.27.…”
Section: Resultsmentioning
confidence: 52%
“…Piezoelectric disks are the functional elements of most UT and AE transducers and their vibration behavior has been studied [ 21 , 31 , 32 , 33 , 34 , 35 ]. However, transmission and receiving sensitivities of a disk element are difficult to find.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonance-antiresonance peaks of SGBT and SCBT appear, respectively, at 184 kHz and 186 kHz. A high angle indicates the fully poled state of the specimen [ 38 ]. The position generated the resonance-antiresonance peak and the maximum phase angle also converts with the introduction of other additives.…”
Section: Resultsmentioning
confidence: 99%
“…ceramic located at morphotropic phase boundary (MPB) where Zr:Ti is of 52:48, possesses a high piezoelectric activity (d 33 up to 300 pC/N) and good temperature stability, and becomes an extremely popular dielectric material[61][62][63]. In addition, other ceramic compositions such as PZT 65/35, 70/30 also received more attention and no limitation by piezoelectric properties[64,65].…”
mentioning
confidence: 99%